Management of Urinary Incontinence Following Radical Prostatectomy: Challenges and Solutions - Castellan P; Ferretti S; Litterio G; Marchioni M; Schips L (Dove Medical Press, 2023)
Pietro Castellan,1 Simone Ferretti,2 Giulio Litterio,2 Michele Marchioni,1,2 Luigi Schips1,2 1Department of Urology, ASL02 Abruzzo, Chieti, Italy; 2Department of Medical, Oral and Biotechnological Sciences, G. d'Annunzio University of Chieti, Urology Unit, Chieti, ItalyCorrespondence: Simone Ferretti, Department of Medical, Oral and Biotechnological Sciences, G. d'Annunzio University of Chieti, Urology Unit, Chieti, Italy, Tel +393278733805, Fax +390871357756, Email ferretti.smn@gmail.comAbstract: Urinary incontinence is a common and debilitating problem in patients undergoing radical prostatectomy. Current methods developed to treat urinary incontinence include conservative treatments, such as lifestyle education, pelvic muscle floor training, pharmacotherapy, and surgical treatments, such as bulking agents use, artificial urinary sphincter implants, retrourethral transobturator slings, and adjustable male sling system. Pelvic floor muscle exercise is the most common management to improve the strength of striated muscles of the pelvic floor to try to recover the sphincter weakness. Antimuscarinic drugs, phosphodiesterase inhibitors, duloxetine, and a-adrenergic drugs have been proposed as medical treatments for urinary incontinence after radical prostatectomy. Development of new surgical techniques, new surgical tools and materials, such as male slings, has provided an improvement of outcomes after UI surgery. Such improvement is still ongoing, and the uptake of new devices might lead to even better outcomes after UI surgery.Keywords: urinary incontinence, radical prostatectomy, pelvic muscle floor exercise, artificial urinary sphincter, male slings, anticholinergic agents, PDE5 inhibitors, duloxetine